2009
DOI: 10.1145/1461928.1461951
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of computing a Nash equilibrium

Abstract: We resolve the question of the complexity of Nash equilibrium by showing that the problem of computing a Nash equilibrium in a game with 4 or more players is complete for the complexity class PPAD. Our proof uses ideas from the recently-established equivalence between polynomialtime solvability of normal-form games and graphical games, and shows that these kinds of games can implement arbitrary members of a PPAD-complete class of Brouwer functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
897
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 583 publications
(911 citation statements)
references
References 17 publications
10
897
1
3
Order By: Relevance
“…Furthermore, these mixed strategies can be easily computed with linear programming. In contrast, we now know that Nash equilibria are hard to compute in general, even for two-person non-zerosum games [DGP06,CDT06]-and consequently for three-person zero-sum games. Von Neumann's minmax theorem [Neu28] seems to have very narrow applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these mixed strategies can be easily computed with linear programming. In contrast, we now know that Nash equilibria are hard to compute in general, even for two-person non-zerosum games [DGP06,CDT06]-and consequently for three-person zero-sum games. Von Neumann's minmax theorem [Neu28] seems to have very narrow applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the complexity results in this area have been almost uniformly negative. A series of papers has shown that it is PPAD complete to compute Nash equilibria, even in 2 player games, even when payoffs are restricted to lie in {0, 1} [7,1,6].…”
Section: Introductionmentioning
confidence: 99%
“…A stronger notion of approximation was introduced in [4], namely -well-supported equilibria. We do not consider this approximation concept here.…”
Section: Notation and Definitionsmentioning
confidence: 99%
“…In a series of works [8,4,2], it was established that computing a Nash equilibrium is PPAD-complete even for two-player games. The focus has since then been on algorithms for approximate equilibria.…”
Section: Introductionmentioning
confidence: 99%